Identity, Indigeneity and "Mythologerm": Reading the Stories of Satyajit Ray's Professor Shonku as Postcolonial Science Fiction. Issue 1 (2nd January 2022) - Karmakar, Goutam; Ghosh, Tanushree
ABSTRACT: Satyajit Ray's Professor Shonku stories depict the futuristic inventions and wondrous journeys of Professor Trilokeshwar Shonku, a renowned Bengali scientist of international acclaim. Shonku makes multiple transatlantic journeys, as seen in those stories, for representing Indian research in the international scientific community. His groundbreaking innovations, such as the miracurall pill, the annihilin pistol, and the omniscope, evoke admiration and envy among European scientists, and his scientific undertakings juxtapose Western laboratory-based sciences with a variety of indigenous and local epistemologies. By investigating some of the stories of Professor Shonku, this paper strives to depict how these stories subvert the western genre of science fiction by legitimizing "native knowledge, " possessed by Professor Shonku as well as other characters as scientific and rational. Within the context of postcolonial literature, this paper also aims to locate Ray's Professor Shonku stories in the tradition of Bangla "kalyavigyan." Furthermore, this paper attempts to study selected stories of Professor Shonku to delineate how the stories embody anti-colonial nationalism in the representation of India, project the postcolonial notion of "alternative modernities" and indigenize the genre of SF through the juxtaposition of indigenous epistemologies as well as myth and folkloric traditions.